28 Haemodynamic performance of supra-annular versus intra-annular transcatheter heart valves in failed bioprostheses. (24th April 2016) - Silaschi, M; Wendler, O; Castro, L; Aldalati, O; Reichenspurner, H; Blankenberg, S; Schaefer, U; MacCarthy, P; Conradi, L
Abstract : Background: Transcatheter aortic valve-in-valve implantation (ViV) is increasingly used to treat failed bioprostheses (BP), but elevated gradients remain a challenge. In-vitro studies suggest transcatheter heart valves (THV) with supra-annular position improve haemodynamic results compared to THV with intra-anular position. Methods: We compared haemodynamic performance. Methods: Since 2008, 71 patients underwent ViV using the Medtronic CoreValve /Evolut-R (CV) or Edwards Sapien /XT/3 THV (ES). Patients were matched regarding true internal diameter (ID) and mode of degeneration (MoD) (CV=22, ES=19). Results: In the total group, CV were implanted into smaller BP than ES (true ID: 19.0 ± 2.1mm vs. 21.4 ± 2.7mm, p < 0.01). After matching, true ID was 19.4 ± 2.0mm in both groups, p = 0.92. MoD, BSA and left ventricular function were not significantly different. Baseline mean gradients (CV: 39.0 ± 17.2mmHg vs. ES: 38.0 ± 19.5mmHg, p = 0.86) and indexed effective orifice areas (iEOA; CV: 0.79 ± 0.11cm²/m² vs. ES: 0.80 ± 0.10cm²/m², p = 0.64) were comparable. At discharge, mean gradients were 22.0 ± 7.7mmHg (CV) vs. 20.0 ± 7.8 (ES, p = 0.43) and iEOA: 0.77 ± 0.14 cm²/m² (CV) vs 0.84 ± 0.21cm²/m² (ES, p = 0.28). In CV, 54.5% had a mean gradient ≥20mmHg, compared to 52.6% in ES, p = 1.0. There was no paravalvular regurgitation >1. Conclusion: In retrospect, haemodynamic performance of either CV or ES for ViV was not different and superiority of supra-annular THV remains to be proven. Other factors, such as implantation depth of THV, may be more relevant for haemodynamic outcome and need further investigation.